Kdo se bojí žen v politice? O postojích k politické participaci žen - Marta Vohlídalová; Hana Maříková (Gender a Výzkum, 2018)
Attitudes towards women in politics and gender culture in general have implications for the status of women in politics and their descriptive representation. In the paper we ask what attitudes people have in the Czech Republic towards women in politics and their descriptive representation, how these attitudes have changed across time, and what factors are associated with these changes. We draw mainly on a survey carried out in 2014, and we compare its data with survey data collected in 2006. The analysis indicates that people nowadays seem to be more tolerant of the low representation of women in politics and are less supportive of using active measures to promote women in politics than they were in the past. The analysis also shows that the decline in support for women in politics is by far the most significant among men, especially men with low education and men who assess the living standard of their household as poor. The paper further deals with the possible sources of this shift in attitudes and suggest a hypothesis and topics for further research.